Analisis Proksimat Tepung Jonjot Buah Labu Kuning - Dokri Gumolung; Meiske Naomi Mamuaja (Jurnal Kimia Fullerene, 2018)
The purpose of this study was to measure the levels of protein, fat, fiber, carbohydrates, water and ash, in jumpy flour from pumpkin. Pumpkin strands are part of the pumpkin fruit where the pumpkin seeds are attached to the inside of the fruit flesh. In processing pumpkin as a food, strands often used as waste or waste and is considered as a fruit that is not useful. Pumpkin plants as a minor food commodity, it turns out, are very rich in bioactive compounds which act as anti-oxidants which are very useful for human health, including spikes that have not been maximized until now due to the lack of scientific information on nutrient content and bioactive compounds in pumpkin fruit jots. This research was carried out using laboratory analysis methods with the following stages, determination and sampling, sample preparation, protein content analysis of the gunning method, fat content, fiber content, carbohydrate content and water and ash content by oven drying method. The results of the study showed that jumpy flour from pumpkin had protein content of 1.09%, fat of 5.15%, fiber of 1.27%, carbohydrate of 73.38%, water of 14.68% and ash of 4.45%. The results of this study concluded that pumpkin fruit pumpkin flour can be used as food fortification material to increase nutritional value.